Time-dependent flow of UCM fluid with chemical reaction, thermal-diffusion and diffusion-thermo effects. Issue 2 (25th February 2014) - Awais, M.; Alsaedi, A.; Hayat, T.
Abstract : Purpose: – The authors presented the time-dependent flow of an upper-convected Maxwell (UCM) fluid in the presence of chemical reaction, thermal-diffusion and diffusion-thermo effects. The paper aims to discuss these issues. Design/methodology/approach: – Recent technique namely homotopy analysis method (HAM) is utilized to compute the solution of the problem. Findings: – Chemical reaction has opposite effects on the concentration field for the destructive and constructive cases. The Deborah number acts as a retarding agent. Originality/value: – Combined effects of thermal-diffusion, diffusion-thermo and chemical reaction are analyzed.